Effects of pre-treatments to preserve quality attributes and prolong shelf-life of dried pomegranate arils - Mokapane, Faith Moleboheng (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.